(untitled) (Journal of Nepal Geological Society, 2025)
A plethora of literature regarding flood susceptibility is available but very few of them have considered local places distant from capital cities. Furthermore, the data driven models that use physically based models have limited applicability in data scarce regions. So, this research work attempts to estimate the flood susceptibility of data scarce local government using open source data in frequently inundated Dhangadhi sub metropolitan city in the far western southern plain of Nepal. The relevant factors responsible for flood namely, elevation, slope, aspect, precipitation, distance from river and LULC were identified. Using AHP method, the pairwise comparison matrix was prepared and weights for each factor and their sub class was estimated. Finally, the flood susceptibility map was prepared in open source QGIS environment dividing the region into five zones of very low, low, medium, high and very high susceptibility. The findings show that about 0.74% (1.93 sq. Km) area lies in the very low zone, 5.44% (14.24 sq. Km) in low, 41.13% (107.69 sq. Km) in medium, 51.22% (134.09 sq. Km) in high and 1.45% (3.84 sq. Km) in very high zone. The output of this research work could be helpful for leadership of local government, policy makers and academicians to strengthen flood risk management. It could be the baseline for future studies on flood susceptibility.